2019
DOI: 10.1016/j.celrep.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

CD36-Mediated Metabolic Rewiring of Breast Cancer Cells Promotes Resistance to HER2-Targeted Therapies

Abstract: SUMMARY Although it is established that fatty acid (FA) synthesis supports anabolic growth in cancer, the role of exogenous FA uptake remains elusive. Here we show that, during acquisition of resistance to HER2 inhibition, metabolic rewiring of breast cancer cells favors reliance on exogenous FA uptake over de novo FA synthesis. Through cDNA microarray analysis, we identify the FA transporter CD36 as a critical gene upregulated in cells with acquired resistance to the HER2 inhibitor lapatinib. Accordingly, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 47 publications
(69 reference statements)
4
108
0
Order By: Relevance
“…They showed that inhibition of CD36 could selectively suppress the growth of lapatinib resistant but not lapatinib sensitive cells, both in vitro and in mouse models. Deletion of the CD36 gene in a mouse model of breast cancer significantly attenuated mammary tumor development [166]. These results suggest that CD36 along with other FA transporters may play a role in the acquired resistance mechanisms of cancer cells.…”
Section: The Potential Role Of Fatty Acid Metabolism In Mapk Signalinmentioning
confidence: 73%
See 1 more Smart Citation
“…They showed that inhibition of CD36 could selectively suppress the growth of lapatinib resistant but not lapatinib sensitive cells, both in vitro and in mouse models. Deletion of the CD36 gene in a mouse model of breast cancer significantly attenuated mammary tumor development [166]. These results suggest that CD36 along with other FA transporters may play a role in the acquired resistance mechanisms of cancer cells.…”
Section: The Potential Role Of Fatty Acid Metabolism In Mapk Signalinmentioning
confidence: 73%
“…Although glycolysis and mitochondrial metabolism have been extensively studied in cancer and drug resistance, the role of lipid and fatty acid metabolism has become an emerging topic of interest. Feng et al demonstrated the reprogramming from de novo FA synthesis to exogenous FA uptake in acquired HER2 inhibitor resistance in breast cancer [166]. cDNA microarrays indicated the upregulation of the CD36 receptor, a FA transporter, in lapatinib (dual ERBB1/2 inhibitor)-resistant cells.…”
Section: The Potential Role Of Fatty Acid Metabolism In Mapk Signalinmentioning
confidence: 99%
“…Highly aggressive prostate cancers show high expression of CD36 which facilitates the intake of exogenous FAs, and the subsequent LDs mobilization provokes a significant alteration in intracellular lipid content in terms of acyl-carnitines, monoacylglycerols and other lysophospholipids (95). Other findings have found the breast cancer cells resistant to HER2 therapy upregulate CD36, and thus acquiring an increased lipid metabolism and metabolic plasticity, both crucial for promoting resistant cells the adaptation and survival under nutrient deprivation and drug toxicity (96). Also, hypoxic breast and glioblastoma cells cancer cells upload FAs from the TME.…”
Section: Lipidsmentioning
confidence: 99%
“…In this review, we highlight altered lipid metabolism as an emerging mechanism of resistance to small molecule kinase inhibitor therapy in breast cancer cells. Lipid metabolic rewiring is becoming increasingly recognized as a critical mechanism that promotes the growth and survival of cancer cells [12][13][14][15] and is often associated with maintenance of cancer cell stemness [16,17] and development of chemoresistance [17,18] . It is becoming clear that resistance mechanisms to kinase inhibitors in breast cancer often involve PI3K/ AKT/mTOR pathway hyperactivation [8][9][10][11]19] .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, PI3K/AKT/mTOR pathway plays a critical role in the regulation of several lipid metabolic processes such as FA synthesis [20] , FA uptake [21] , FA storage into lipid droplets [22,23] and FAO [24,25] . Recent reports have demonstrated that targeting lipid metabolic pathways may be a valuable therapeutic strategy to re-sensitize cells resistant to HER2-targeted therapies in breast cancer [18,26,27] . We discuss the rationale behind targeting lipid metabolic rewiring in the treatment of drug resistant breast cancer cells as a therapeutic approach that requires further investigation.…”
Section: Introductionmentioning
confidence: 99%